Gastric Xanthoma – A Case Report - Saha, Madhusudan; Safwath, Syed Alamgir (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Gastric xanthoma, although benign lesion, sometimes resemble to neoplasm. It is more common in older age group. Histologically it contains lipid ladenhistiocytes. But it should be differentiated from malignancy. So proper attention during endoscopic examination and relevant investigations to exclude malignancy should be considered in every patients with gastric xanthoma. J Bangladesh Coll Phys Surg 2023; 41: 237-238